2016
DOI: 10.2113/gssgfbull.187.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Tectono-magmatic reactivation of Téfidet Cretaceous trough during Cenozoic (Aïr, Niger)

Abstract: The Téfidet trough (eastern Niger) belongs to the Ténéré megasystem set of Cretaceous rifts N130°E to N170°E oriented, corresponding to the direction of the Lake Chad-Hoggar tectonic axis. The study of the relationship between the structure of the trough and alkaline fissural volcanism that developed there from the Oligocene to Plio-Quaternary shows the uniqueness of the Téfidet trough compared to the neighboring contemporary volcanic areas of Hoggar, Cameroon, and southern Aïr. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This direction is the second largest direction that has found Bagzan mount [46]. Moreover, in Tefidet trough North-South (NS) of Bagzan, N60˚-N70˚ accident is associated with dykes [47].…”
Section: Discussionmentioning
confidence: 99%
“…This direction is the second largest direction that has found Bagzan mount [46]. Moreover, in Tefidet trough North-South (NS) of Bagzan, N60˚-N70˚ accident is associated with dykes [47].…”
Section: Discussionmentioning
confidence: 99%
“…Many veins of quartz, micro grained rocks or porphyry fill the fractures. Tectonics is manifested by the presence of characteristic structural directions of general orientation: N0˚, N70˚ and N160˚ [27] [28] [29].…”
Section: Geological Contextmentioning
confidence: 99%
“…Several hydrogeological studies [1] [13] [21] [33] have shown the importance of Digital Elevation Model (DEM and satellites images) in the mapping of fractures related to tectonics fracturing and alteration in a location of aquifers in basement area. The DEM stumpage technique has proven its worth in mapping discontinuity of tectonic origins [27]. This approach allowed to improve the visibility of lines and these are reported by manual methods (digitalization).…”
Section: Structures Cartographymentioning
confidence: 99%
See 1 more Smart Citation
“…The Raghane shear system, passing to the eastern part of Agadez city (Figure 8, was the focus of a seismic event on 4 th July 1969 from geophysics interpretation map [15] . There is also a potential seismic zone corresponding to a system of strike slip faults oriented ~N75° (Figures 1 and 8), called "Agadez Lineament" [16] or the Guinean-Nubian Lineament (GNL) [17,18] that passed through the southern part of Agadez city [19,20] .…”
Section: Geological Originmentioning
confidence: 99%